THE ROLE OF GOVERNMENT POLICIES IN MODERATING THE EFFECT OF SOCIAL MEDIA INNOVATION ADOPTION AND ENTREPRENEURIAL ORIENTATION ON PERFORMANCE OF MSMES IN JEWELRY CRAFTS GIANYAR REGENCY - Ni Putu Wedayani Antari; Ni Wayan Ardani; I Dewa Nyoman Usadha (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: Micro, Small, and Medium Enterprises (MSMEs) in jewelry handicrafts in Gianyar Regency are facing the challenge of digital adaptation and increasingly competitive market dynamics. The adoption of social media innovation and entrepreneurship orientation is seen as a strategic factor in improving the performance of MSMEs, but its effectiveness is highly dependent on government policy support. This study aims to analyze the influence of social media innovation adoption and entrepreneurial orientation on the performance of MSMEs, as well as test the role of government policies as a moderation variable. Method: This study uses a quantitative approach with an explanatory design. Data was collected through a questionnaire on 153 jewelry handicraft MSME actors in Gianyar Regency. Data analysis was conducted using Partial Least Square–Structural Equation Modeling (PLS-SEM) to test the direct influence and moderation effect between variables. Results: The results of the study show that the adoption of social media innovation and entrepreneurial orientation has a positive and significant effect on the performance of MSMEs. In addition, government policies have been proven to play a role as a moderation variable that strengthens the influence of the adoption of social media innovations and entrepreneurial orientation on the performance of MSMEs. Policy support in the form of fiscal incentives, access to financing, and digital facilitation increases the effectiveness of MSMEs' internal strategies in producing more optimal performance. Novelty: These findings confirm the importance of synergy between the internal capabilities of MSMEs and government policy support. Social media and entrepreneurship orientation have a stronger performance impact when supported by a conducive and responsive policy environment to the needs of MSMEs in the digital era.